Pengaruh Reog Trimudho Rahayu Terhadap Sikap Sosial Penonton Di Desa Gatak Kecamatan Ampel Kabupaten Boyolali (Universitas Negeri Semarang, 2020)
Reog Trimudho Rahayu art tells about people who fight for throne in the past. This art comes from Boyolali Regency. This study is focused on the show of the Reog Trimudho Rahayu and the influence of the art on social attitudes of society. The aims of this research is to describe the show of the Reog Trimudho Rahayu art and the influence of it in Gatak village, Ampel, Boyolali Regency. Describtive qualitative is used as the method in this study. The approach which is used in the emic ethical approach. Data are collected by doing observation, interview, and documentation. The data are analyzied by using Ashead theory. The validity technique which are used are source triangulation, method triangulation, and time triangulation. The influence of this art on soscial attitudes of society in Gatak village, Ampel, Boyolali Regency is on the form of show. It includes movement, actor, cosmetics and cotumes, music or accompaniment, stage or lighting. Positive attitude includes cooperation, solidarity, and tolerance. The suggestion for Reog Trimudho Rahayu group is creating new innovations in working on movements, music, and clothing so they dont look monotonous, so that people are more enthusiastic to see the Reog Trimudho Rahayu.